Prevalencia de porphyromona gingivalis en el espacio subgingival en pacientes con cardiopatía - Flores Armas, Vanessa Carolina (2018)
The microbiological organism Porphyromona gingivalis is one of the main players in the process of destruction of the periodontal tissue, manipulating the defenses of the host and intervening in the establishment of subgingival disbióticas colonies, also at a systemic level it has become the focus of attention of many researchers , due to its clear implication in the degeneration of pre-established atherosclerotic plaques, aggravating the clinical pictures of patients at risk, by producing local arterial inflammation. The main objective of the study is to determine the prevalence of P. gingivalis bacteria in the subgingival space in patients with heart disease. To compare prevalence and percentage of colonies of P. gingivalis bacteria between patients with heart disease and without heart disease. And finally determine the risk factors that increase the prevalence of the bacteria in at-risk patients. Method: Biological samples were taken in the subgingival space in 30 healthy patients and in 30 patients with any variety of cardiovascular disease with paper cones 30 and 25, the samples were incubated for 3 days in thioglycollate to create bacterial proliferation, and they were sown and cultured on blood agar for two more weeks. Results: 80% of patients with cardiovascular disease -PxECV (+) – gave positive results for P. gingivalis in the culture performed, while in patients without cardiovascular disease -PxECV (-) - had a positive result of 40%, making it clear that P. gingivalis is present in the subgingival space both in patients with heart disease and in patients without heart disease, being the same a bacterial agent with great ability to complicate the clinical picture of patients with cardiovascular disorders. In addition to concluding that the number of bacterial colonies per culture box is much higher in the results of the study group, compared to those of the control group.